English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-01-27 04:25:07 · 28 answers · asked by Doug 2 in Science & Mathematics Mathematics

28 answers

First: eliminate parenthesis > multiply the outer terms with the terms in parenthesis...

(2x)(2x) + (2x)(1) - (x)(3x) - (x)(- 2)

4x^2 + 2x - 3x^2 - (-2x)

4x^2 + 2x - 3x^2 + 2x

Sec: combine "like" terms...

4x^2 - 3x^2 + 2x + 2x

= x^2 + 4x

2007-01-27 04:30:12 · answer #1 · answered by ♪♥Annie♥♪ 6 · 2 0

LOL...smiles...you can't use a calculator to solve that equation!

2x(2x +1) - x(3x - 2) =
4x^2 +2x -3x^2 +2x =
x^2 + 4x

2007-01-27 12:32:26 · answer #2 · answered by Pooky 4 · 0 0

2x(2x + 1) - x(3x - 2) =

Multiplying into the parenthesis (general rules: a(b + c) = ab + ac, a(b - c) = ab - ac )

4x^2 + 2x - (3x^2 - 2x) =

4x^2 + 2x - 3x^2 + 2x =

Adding/subtracting similar terms together:

x^2 + 4x

2007-01-27 12:37:18 · answer #3 · answered by jcastro 6 · 0 0

=4x^2 +2x -3x^2+2x
=(4-3)x^2 +(2+2)x
=x^2 +4x
=x (x +4) x1=0 , x2= - 4

2007-01-27 12:34:29 · answer #4 · answered by Tuncay U 6 · 0 0

= (4x^2 + 2x) - 3x^2 +2x
= x^2

2007-01-27 12:31:04 · answer #5 · answered by clearlyalienboy 2 · 0 0

Best Answer - Chosen by Asker

Multiply it out:

x^2 - 2x - 3 = x^2 - 3x + 2

The x^2 terms cancel out, so

-2x - 3 = -3x + 2

Add 3x to both sides:

x - 3 = 2

Add 3 to both sides:

x = 5

2007-01-27 12:29:39 · answer #6 · answered by Anonymous · 0 2

multiply the numbers before the parenthesis to the numbers in the parenthesis:

= 4x^2 + 2x -3x^2 +2x

add similar terms together to get:

= x^2 + 4x

2007-01-27 12:29:34 · answer #7 · answered by spidermilk666 6 · 1 0

2x*2x+1*2x-x*3x+2x=4x^2+2x-3x^2+2x

4x^2+2x-3x^2+2x=4x^2-3x^2+2x+2x

4x^2-3x^2+2x+2x=x^2+4x

x^2+4x and in a simpler form x(x+4)

2007-01-27 12:34:52 · answer #8 · answered by Michelle M 2 · 0 0

2x(2x + 1) - x(3x - 2)
= 4x^2 +2x-3x^2+2x
= x^2+4x


note: x^2 is x squared

2007-01-27 12:29:25 · answer #9 · answered by desirooo58 3 · 1 2

2x(2x+1)-x(3x-2)


2x(2x+1)-x(3x-2)=4x^2+2x-3x^2+2x

= x^2+4x= x(x+4)

2007-01-27 12:39:48 · answer #10 · answered by dheeru 2 · 0 0

fedest.com, questions and answers